State of the planet the complete series - Attenborough, David ([London] BBC Worldwide Ltd., 2005)
Deforestation, global warming, depletion of aquifers, rising sea levels, and mass extinctions--how much longer can Earth compensate for these damaging forces? In this timely three-part series, David Attenborough and some of the world's leading experts on environmental matters consider probably the most important issue of the 21st century: the future of life on this planet.
Part1. Is there a crisis? -- part 2. Why is there a crisis? -- part 3. Future of life.
Originally broadcast as a BBC Production in 2000
Keywords: Earth (Planet); Earth sciences; Environmental protection; Conservation of natural resources; Documentary films